Digital Academics as Strengthening Religious Moderation Values in Overcoming the Potential of Identity Politics in The Kadokan Village Community, Sukoharjo District - Mahfiyana, Layyin; Ariyani, Evi; Rahmatullah, Lutfi; Yufidz Anwar Ibrohim , Mohammad (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service aims to investigate the role of digital academics in strengthening the values of religious moderation as a response to the potential for identity politics in the community of Kadokan Village, Sukoharjo Regency. Identity politics is often a source of tension and conflict in various communities, especially in religious contexts. A qualitative approach was used in this research by collecting data through in-depth interviews, participant observation, and content analysis of digital platforms used by academics and local communities. The results of UIN Raden Mas Said's Community Service (PKM) regarding "Digital Academics as Strengthening the Values of Religious Moderation in Countering the Potential for Identity Politics in the Kadokan Village Community, Sukoharjo Regency" in terms of activities have run smoothly, on target, and in accordance with PKM planning. This activity also provides a positive and real influence by indicating openness in the way the community views the meaning of difference and plurality. The next step is an evaluation to see whether the level of tolerance in the PKM location area is increasing and whether moderate attitudes are also growing